Morphological data and molecular characterization of Lagostonema ecasiense (Nematoda, Molineidae) parasite of Lagostomus maximus (Rodentia, Chinchillidae) from Argentina and other considerations - Victoria Canova; María Celina Digiani; Rocío Callejón Fernández; Darío Balcazar; Natalia Beatriz Guerreiro Martins; Agustín Manuel Abba; María del Rosario del Rosario Robles (Parasitology)
Lagostonema ecasiense is a bursate nematode parasite of Lagostomus maximus in Argentina. New morphological data, geographical distribution, ecological data, molecular characterization and exploratory phylogenetic analysis are provided. The general morphology and measurements agree with the original description with minimal discrepancies. The geographical distribution of Lagostonema is expanded with 3 new provinces and 9 new departments in Argentina. The molecular characterization constitutes the first molecular contribution for the genus Lagostonema. The analysis of genetic distances and phylogenetic exploration allow considering L. ecasiense as a nominal species, confirming its nomenclatural taxonomic identity. Likewise, although morphological studies allow the identification of specimens from all populations as L. ecasiense, molecular studies show a major genetic distance in the population from Santiago del Estero Province concerning the rest of the populations. Consequently, the haplotypes are mentioned as Lagostonema sp. with the possibility that these specimens belong to a new species. This study is valuable because it contributes to the ratification of a nominal species described decades ago, adding new morphological aspects and providing an understanding of their value as a marker of host populations.